2016
DOI: 10.1071/he16082
|View full text |Cite
|
Sign up to set email alerts
|

Nurse provision of support to help inpatients quit smoking

Abstract: Issue addressed Identification of the factors that facilitate nurses to provide smoking cessation advice to hospitalised patients. Method Six semistructured focus groups with 26 nurses were conducted in June 2015. Participants completed a structured survey to collect patient demographic data and assess attitudes towards their role in addressing smoking cessation among inpatients. Results Important themes that emerged from the qualitative data were: nurses' negative perceptions of smokers, nurses' confidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“… 21 An apparent lack of clarity around whose role it is to provide smoking cessation care for inpatients was reflected in a study involving focus group discussions with 26 nurses. 19 The study also found that nurses expressed a lack of confidence about their knowledge in smoking cessation care which may prevent them from consistently addressing cessation with all patients. 19 Commitment and support from all clinical and administrative staff may require adjustment to existing roles to promote a multilevel approach to smoking cessation care across health services.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“… 21 An apparent lack of clarity around whose role it is to provide smoking cessation care for inpatients was reflected in a study involving focus group discussions with 26 nurses. 19 The study also found that nurses expressed a lack of confidence about their knowledge in smoking cessation care which may prevent them from consistently addressing cessation with all patients. 19 Commitment and support from all clinical and administrative staff may require adjustment to existing roles to promote a multilevel approach to smoking cessation care across health services.…”
Section: Discussionmentioning
confidence: 92%
“… 19 The study also found that nurses expressed a lack of confidence about their knowledge in smoking cessation care which may prevent them from consistently addressing cessation with all patients. 19 Commitment and support from all clinical and administrative staff may require adjustment to existing roles to promote a multilevel approach to smoking cessation care across health services. 22 The development of smoking cessation clinical guidelines and protocols, supported by staff training and regular monitoring and evaluation, will facilitate implementation of smoking cessation care into routine practice.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, the efficacy of training courses to motivate nurses and make them proactive in improving their knowledge about smoking cessation counselling is acknowledged. For this reason, it is strongly recommended that nurses' training includes time and incentive to undertake such activities (Malone et al, 2017).…”
Section: Discussionmentioning
confidence: 99%